The Gods Sleep Through It All : A collection of essays - Guchu, Wonder, 1969- (Book collections on Project MUSE., 2019)
It has been said before that Africa is one of the richest continents in the world but the poorest and colonialism was blamed for Africa's problems before the continent was liberated. Although some leaders still blame colonialism for the poverty that is ravaging the continent today, it cannot be denied that poor governance, corruption, greed among many other ills are causing Africa's current problems. The essays in this collection The Gods Sleep Through It All discusses Africa's leadership problems and how most countries still rely on former colonisers for help despite boasting of untold natural wealth. The essays discuss the corruption of political parties and politics in Africa and question why African countries readily open their arms to countries like China but close borders to people from other African countries.